Analisis Kesiapsiagaan Masyarakat Dalam Menghadapi Bencana Banjir Di Kelurahan Panunggangan Barat Kecamatan Cibodas Kota Tangerang - Tasyani Khairunisa; Alwin Alwin (Universitas Prof. Dr. Hazairin, S.H, 2022)
This research is entitled “Community Preparedness Analysis flood in the village of west panunggangan in the Cibodas district Tangerang City” The purpose of this research is know preparedness community to flood in the village of west panunggangan in the Cibodas district Tangerang City. This research uses the method quantitative descriptive. The population in this research is people in vulnerable areas fllod in the village of west panunggangan in the Cibodas district. Primary data obtained from field observation, questionnaire distribution, and documentation, while secondary data obtained from document study and literature review. Research results show that community preparedness in the village of west panunggangan in the Cibodas district Tangerang City can say it's almost ready, This can be seen from the programs implemented by the community about the preparedness program in dealing with flood disasters in the village of west panunggangan in the Cibodas district Tangerang City.